INOVASI MEDIA PEMBELAJARAN MENGGUNAKAN BOOK CREATOR DI SDN PERCOBAAN PADANG - Ainila Pradi Sespen; Firman; Desyandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Interactive learning media can be a solution for students in learning. According to Sumiharsono (2017: 57) the use of media as a means of conveying information, both audio, visual and audio-visual so that it can stimulate thinking and learning findings for students, therefore the use of technology as audio, visual, and audio-visual learning media can be a solution for information delivery in the field of Education. During the trial process, the researcher wrote down important things about what obstacles occurred when implementing book makers in class V at SDN Pertryan Padang. After applying it, students are then given a test to find out the level of understanding of the material from the author of this book. To find out the level of student understanding, the researchers asked questions to students and the authors designed and made questionnaires for students who still did not understand the material that had been delivered through the book creator. The use of book creators in Pancasila Education subjects at SDN Percobaan Padang can be optimally utilized. This is because the school has facilities that are quite supportive in the operation of this book-making media, such as the availability of projectors, laptops and speakers in the school. This book-making media can be used in online learning, making it easier for teachers to convey learning and students understand what the teacher explains.